Fundamentals of gas dynamics. - Emmons, H. W. (Howard W.) (High speed aerodynamics and jet propulsion, 1958)
Volume II of the High Speed Aerodynamics and Jet Propulsion series. The series which stress the more fundamental aspects of the various phenomena that make up the broad field of aeronautical science. The aerodynamicist and gas dynamicist will find both the classical and the important new concepts of gas dynamics presented in an informative and stimulating manner. Specialists in the study of gas dynamics have contributed Sections as follows: H.S. Tsien, The Equations of Gas Dynamics; L. Crocco, One-Dimensional Treatment of Steady Gas Dynamics; A. Kantrowitz, One-Dimensional Treatment of Nonsteady Gas Dynamics; W. Hayes, The Basic Theory of Gasdynamic Discontinuities; H. Polachek and R.J. Seeger, Shock Wave Interactions; H.G. Stever, Condensation Phenomena in High Speed Flows; T.H. Von Karman, H.W. Emmons, G.I. Taylor, and R.S. Tankin, Gas Dynamics of Combustion and Detonation; S. Schaaf and P. Chambre, Flow of Rarefied Gases. Originally published in 1958. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.